Scientific Paper Pelatihan Penulisan Karya Tulis Ilmiah bagi Mahasiswa Keperawatan STIKES Alifah Padang - Asri Wahyuni Sari; Ria Satini; Risa Yulisna; Suci Dwinitia; Afrini Rahmi - (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Writing activities are very important, especially for students in every lecture process. Assignments given by lecturers generally require students' writing skills. Writing skills that are important to be mastered by students, especially final semester students, are writing scientific papers. Scientific writing is one of the requirements for students to complete their education level. The activity of writing a final project in the form of a scientific paper is a form of embodiment of students' understanding and skills during lectures. Courses related to writing are only in the form of general delivery. The purpose of this service is to help students understand the correct procedure for writing scientific papers so that the problems discussed in the scientific papers they write can be conveyed and understood well by the readers.